In silico antibody-peptide epitope prediction for personalized cancer therapy - Jacobs, Ivan; Ming, Lim Chwee; Mong, Jamie; Maragoudakis, Manolis; Malik, Nishant (Frontiers in Applied Mathematics and Statistics, 2023)
The human leukocyte antigen (HLA) system is a complex of genes on chromosome 6 in humans that encodes cell-surface proteins responsible for regulating the immune system. Viral peptides presented to cancer cell surfaces by the HLA trigger the immune system to kill the cells, creating Antibody-peptide epitopes (APE). This study proposes an in-silico approach to identify patient-specific APEs by applying complex networks diagnostics on a novel multiplex data structure as input for a deep learning model. The proposed analytical model identifies patient and tumor-specific APEs with as few as 20 labeled data points. Additionally, the proposed data structure employs complex network theory, and other statistical approaches that can better explain and reduce the black box effect of deep learning. The proposed approach achieves an F1-score of 80% and 93% on patient one and two respectively and above 90% on tumor specific tasks. Additionally, it minimizes the required training time and the number of parameters.